Die Gräber von Bat und Al-Ayn und das Gebäude II in Bat - Döpper, Stephanie, (Arabia orientalis ;, 2021)
The Early Bronze Age in third-millennium-BC Eastern Arabia was a period of fundamental change, which is apparent in the development of social complexity, the exploitation of new resources and the emergence of new modes of life. Hallmarks of this period include monumental structures, so-called towers, and stone-built circular tombs. The second volume of the series Arabia Orientalis is dedicated to the archaeological investigation of the Early Bronze Age necropolises of the UNESCO world heritage sites Bat and Al-Ayn in the Sultanate of Oman, as well as the monumental tower structure Building II at Bat. It encompasses detailed reports on the architecture and stratigraphy, as well as the find assemblages from the excavated buildings, including pottery and small finds, along with anthropological as well as anthracological studies.